2019
DOI: 10.1159/000500191
|View full text |Cite
|
Sign up to set email alerts
|

The International Academy of Cytology Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy Cytopathology: A Single Institutional Retrospective Study of the Application of the System Categories and the Impact of Rapid Onsite Evaluation

Abstract: Objectives: To review the performance and utility of the International Academy of Cytology (IAC) Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy (FNAB) Cytology five category stratification and evaluate the impact of rapid onsite evaluation (ROSE). Method: A retrospective analysis of breast FNAB cytology cases with matched histopathological results at a single institution over a 32 months period using a structured reporting system with 5 diagnostic categories (“inadequate/insufficient,” “ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
93
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(131 citation statements)
references
References 25 publications
23
93
2
3
Order By: Relevance
“…The reported ROM of the benign cytological category is possibly increased as a consequence, resulting in lower reported specificity of FNAB. Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported ROM of the benign cytological category is possibly increased as a consequence, resulting in lower reported specificity of FNAB. Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…With experience and good smear preparation technique, the diagnostic accuracy is satisfactory. The turn‐around time may be shortened even further using Rapid On‐site Examination (ROSE), either routinely or under special conditions 15 . The short turn‐around time combined with the high accuracy is especially useful in places where breast cancer patients have limited access to health care facilities or have access to facilities with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the cytopathological interpretation is also of great importance and studies of other categorization systems at other body sites have shown variability in interobserver agreement [13-15]. While the ROM and predictive values for the IAC YSRB have been reported [7, 8, 16], little information is available on the interobserver reproducibility of the 5 categories. In this study, we report the interobserver reproducibility of these IAC YSRB categories.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [ 17 , 18 ] indicated that the Risk of Malignancy (ROM) for the first three categories (insufficient material, benign and atypical) is low (ROM = 2.6–15%). In contrast, the ROM for breast lesions regarded as suspicious or malignant using the IAC Yokohama system ranges from 84.6 to 100%.…”
Section: Methodsmentioning
confidence: 99%